Detecting therapeutic improvement early in therapy: validation of the SCORE‐15 index of family functioning and change. Issue 1 (12th September 2013) - Stratton, Peter; Lask, Judith; Bland, Julia; Nowotny, Ewa; Evans, Chris; Singh, Reenee; Janes, Emma; Peppiatt, Anneka
<x xml:space="preserve">Abstract</x> The SCORE index of family functioning and change is an established measure, with strong psychometric properties, of the quality of family life. We report the sensitivity to therapeutic change of the short form, the SCORE‐15. Data are reported from 584 participants aged above 11 years, representing 239 families. All couples and families had been referred for systemic couples and family therapy, completing the form at start of the first session and close to the fourth. The SCORE‐15 is shown to be acceptable with strong consistency and reliability. Change over only three sessions was highly statistically significant. Further validation is provided by improvements in quantified scores correlating significantly with independent measures provided by family members and by their therapists. The SCORE‐15 is a proven measure of therapy and of therapeutic change in family functioning. It is therefore a routinely usable tool applicable to service evaluation, quality improvement, and to support clinical practice. Practitioner Points The SCORE provides practitioners with brief descriptions of varied aspects of family interaction that have proven significance for many families who present for therapy. SCORE‐15 can be used with confidence to monitor and report proven indicators of progress in systemic therapy. Because SCORE identifies clinically significant issues of family interaction it has many potential uses in therapy. There are many new possibilities for therapists to undertake collaborative research.